SpaceWire driver and ECSS protocol handling for mission-critical applications running on a LEON4 processor - Ludwig von Feilitzen (2023)
The SpaceWire communication protocol simplifies the design of communication systems to be deployed in space. It can be used in conjunction with higher level protocols that further specify how two SpaceWire nodes can communicate with each other. In order to do this both nodes need the correct drivers which allows them to create and understand communication in the format of the protocol. This document is the result of a thesis project within the scope of which such a driver has been developed. The driver is tested with the help of a test-bench, the creation of which is also a part of the project. The driver is written for a GR740 System-on-a-Chip and adheres to the RMAP protocol specification.
Keywords: SpaceWire; ECSS; RMAP; GR70; LEON4